Results of Infrainguinal Bypass with a Composite Graft Combining Polytetrafluoroethylene and Vein Graft in Absence of Appropriate Saphenous Vein Graft - Myung Jae Jin; Ui Jun Park; Hyoung Tae Kim; Young-Nam Roh (Vascular Specialist International, 2017)
Purpose: Use of a composite graft combining a polytetrafluoroethylene graft with an autogenous vein is an option for limb salvage in the absence of an adequate single segment vein graft. We aimed to investigate the results of infrainguinal bypass with a composite graft.